Molecular Spectroscopic (FTIR and UV-Vis) Analysis and In Vitro Antibacterial Investigation of a Deep Eutectic Solvent of N,N-Dimethyl Urea-Citric Acid - Yudha S., Salprima; Angasa, Eka; Reagen, Muhamad Alvin; Kazi, Mohsin (Science and Technology Indonesia, 2024)
The intriguing pursuit of environmentally friendly solvents with tailored properties for diverse applications is a focal point of numerous studies, encompassing precursor selection, thorough characterization, and the exploration of potential applications. The study aims to assess the physicochemical properties and antimicrobial activity of deep eutectic solvents (DES) produced from N,N-dimethyl urea (DMU) and citric acid (CA), highlighting differences from their individual precursors. Various mass ratio variations of (DMU, solid) and (CA, solid) (DMU:CA = 1.0:1.0; 1.0:1.5; 1.0:2.0; 2.0: 1.0; 1.5:1.0) have been tested to make DES solvents through the melt process. Both types of blends generally melt at a temperature of 80°C. The overall liquid resulting from the melting of solids was generally clear in color. Molecular analysis using an infrared spectrophotometer showed some insignificant shifts from one product to another, compared with DMU and CA as precursors. Likewise, analysis using a UV–Vis spectrophotometer, when the entire sample was dissolved in demineralized water (2 mg/mL), showed no difference in the spectrum. In addition, functional group analysis using a spectrophotometer showed some minor changes, mainly shifts in peaks due to changes in the DMU:CA ratio. This may be due to the interaction of the hydrogen donor and the hydrogen acceptor in DES. All samples showed absorption peaks in the ultraviolet region of 202-210 nm. The resulting DES application showed growth inhibitory activity for Staphylococcus aureus and Escherichia coli bacteria in all products produced. The same analysis of the two types of precursors used showed that only CA had activity, but DMU did not have similar activity.